Assessing the Quality of Care Delivered to Transgender and Gender Diverse Patients with Cancer in Ireland: A Case Series. (19th December 2020) - Moloney, Carolyn; Allen, Margaret; Power, Derek G.; M. Bambury, Richard; O'Mahony, Deirdre; O'Donnell, Dearbhaile M.; O'Reilly, Seamus; Collins, Dearbhaile C.
Abstract: Introduction: "Transgender" and "gender diverse" are umbrella terms encompassing those whose gender identities or expressions differ from those typically associated with the sex they were assigned at birth. There is scant global information on cancer incidence, outcome, and mortality for this cohort. This group may present with advanced cancer, have mistrust in health care services and report anxiety and depression at higher frequencies, a finding often seen in marginalized groups because of minority stress. Materials and Methods: Medical oncologists were contacted by secure email to identify patients who self‐identify as transgender and gender diverse in three Irish hospitals. Five patients were identified. A retrospective chart review was conducted and a pseudonymized patient survey was distributed. Results: All patients included in our chart review ( n = 5) were diagnosed with advanced disease on initial diagnosis. Two patients identified as men, two as women, and one as a transwoman. Two of five patients' health record charts reflected a name or gender change. Three patients had gender transitioning treatment postponed. Assessing comorbidities, it was seen that four patients required psychiatry input. Predominant issues noted in our patient survey by the two respondents ( n = 2) were "mis‐gendering, " lack of a gender‐neutral hospital environment, lack of inclusion in cancer groups, and barriers in changing name and/or sex on hospital records. Conclusion: Components of care requiring revision include patient accessible pathways to change names and gender on health records, earlier access to psychological support and targeted screening and support groups. Resources for hospital staff to improve awareness of correct terminology and to provide gender neutral facilities are worthwhile. Implications for Practice: The implications for practice on an international level include patient‐friendly pathways for changing hospital name and gender so that patients may feel comfortable using wristbands. The need for international screening guidelines for transgender patients and national transgender cancer support groups is highlighted. On a day‐to‐day level for providers, the correct use of pronouns makes a big difference to patients. Asking about preferred pronoun on first visit and noting on patient's file is worthwhile. It is important for providers to know that increased psychological support should be offered early on first clinic visit and engaged with as necessary when patient has a history of anxiety or depression. Providers should discuss openly that some gender transitioning treatment will be postponed because of cancer care and refer to both the physical and psychological sequelae of this. Asking transgender patients which room or bathroom they would prefer when rooms are gendered is essential. Abstract : Transgender and gender diverse people are more likely to present with advanced cancer. This group of patients reports anxiety and depression at higher rates and mistrust in the health care system. This article reports on the issues affecting cancer care for this cohort, aiming to raise awareness and improve cancer care in this patient group.